Decentralization of education: the experience of Kenyan secondary schools - Mulwa, David M.; Kimiti, Richard Peter; Kituka, Titus M.; Muema, Elizabeth M. (My University, 2011)
Kenya has undertaken several educational reforms since independence in 1963. Several committees, commissions and task forces have been set up over the years with the mandate to make suitable recommendations on how to overcome the ever rising challenges facing the Kenyan education. The necessary legal and policy guidelines have also been prepared to guide the administration, management and governance of education, in line with the country’s educational philosophy. The latest educational reform of 2005 was geared towards decentralization of education. For this paper, decentralization is limited to the transfer of decision-making authority to stakeholders at the secondary school level. This paper therefore gives a brief history of educational reforms in Kenya, discusses the challenges facing the Kenyan education, the concept of decentralization and the limitations of secondary schools to promoting it. Lastly, it makes recommendations on what should be done for secondary schools to fully embrace the concept of decentralization in Kenya
Keywords: Challenges; Decentralization; Democratization.